The Influence of Parasitic Disease (Intestinal Giardiasis) On the Course of Atopic Dermatitis - Nijazova Tajigul Axmetovna; Imamova Ilmira Abdullaevna (International Journal of Medical Science and Public Health Research, 2026)
When characterizing the combined clinical course of atopic dermatitis with intestinal giardiasis, eosinophilia and an increase in the level of total serum Ig E (141±12 IU/ml) were established. The detected increase in the level of immunoglobulin E in patients with intestinal giardiasis served as the basis for prescribing three-time coproscopy to patients with atopic dermatitis to detect and completely eliminate parasitoses, which will increase the effectiveness of specific therapy for atopic dermatitis. It has been established that in case of atopic dermatitis, treatment of intestinal giardiasis is preferably carried out using nifuratel. In patients with atopic dermatitis, the effectiveness of treatment for intestinal giardiasis was established, which was manifested in the disappearance of atopic dermatitis on the 7-8th day of treatment.